Peningkatan Kemampuan Membaca dan Memahami Nasehat Tenas Effendy pada Siswa SMA : Peningkatan Kemampuan Membaca dan Memahami Nasehat Tenas Effendy pada Siswa SMA - Amanan; Hermansyah; Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2025)
Pantun, as a form of Malay oral literature, holds significant aesthetic, educational, and moral values. One prominent type is the pantun nasehat (advisory verse), which functions as a medium for conveying ethical teachings in Malay culture. However, interest and ability among younger generations, particularly students at SMA Negeri 3 Siak Hulu in reading and understanding this form of pantun remain limited. This community service program aimed to enhance students' literacy skills regarding Pantun Nasehat by Tenas Effendy through educational approaches involving lectures, discussions, and hands-on practice. The results showed a significant improvement in students’ understanding of the structure, meaning, and function of pantun nasehat. Based on pretest and posttest evaluations, all participants demonstrated positive progress in their knowledge and appreciation of pantun as a valuable element of Malay cultural heritage. This program also helped strengthen local cultural identity and sparked student interest in preserving oral traditions that are increasingly marginalized by modern developments.